Effects of Mimosa (Mimosa invisa) Compost and Phosphorus on the Yield and Yield Components of Lentil (Lens culinaris L.) - Barua, R; Bhuiya, MSU; Kabir, MM; Maniruzzaman, S; Ahmed, Z (The Agriculturists, 2012)
An experiment was conducted at the Agronomy Field Laboratory of Bangladesh Agricultural University, Mymensingh, during November 2008 to March 2009 to examine the effects of mimosa (Mimosa invisa) compost and phosphorus on the yield and yield components of lentil variety BARI Masur6. Two factors were: a) Mimosa invisa compost and b) phosphorus fertilizer. Mimosa invisa compost were used in four rates- 1 (M1), 5 (M2), 10 (M3) and 15 (M4) t ha-1. Five rates of phosphorus fertilizer were: ‘no’ phosphorus (P0), 25% RDP (P1), 50% RDP (P2), 75% RDP (P3) and 100% recommended dose phosphorus (TSP @ 85 kg ha-1) (P4). The experiment was laid out in a factorial randomized complete block design with three replications. Mimosa invisa compost had significant effect on the crop characters except number of branches plant-1. The highest seed yield (1435.33 kg ha-1) was observed in M2 treatment (5 t ha-1) and the lowest seed yield (1220 kg ha-1) was observed in M4 treatment (15 t ha-1). Phosphorus had a significant effect on all the plant characters. The highest seed yield (1464.17 kg ha-1) was observed in P4 treatment (100% RDP) and the lowest was observed in P0 treatment. The interaction effect of Mimosa invisa compost and phosphorus on the yield of lentil was significant. The highest seed yield was observed (1630 kg ha-1) in M2×P4 treatment and the lowest was in M3×P0 treatment (1000 kg ha-1). Keywords: Lentil; Mimosa invisa compost; phosphorus; yield; yield components DOI: http://dx.doi.org/10.3329/agric.v9i1-2.9480 The Agriculturists 2011; 9(1&2): 63-72